17β-Estradiol Promotes Apoptosis of HepG2 Cells Caused by Oxidative Stress by Increasing Foxo3a Phosphorylation - Guo, Yusheng; Cai, Xiangsheng; Lu, Hanwei; Li, Qiqi; Zheng, Ying; Lin, Zefang; Cheng, Zexiong; Yang, Maoxiang; Zhang, Li; Xiang, Lei; Yang, Xiaorong (Frontiers in Pharmacology, 2021)
Liver cancer is associated with high mortality, particularly in patients infected with the hepatitis B virus. Treatment methods remain very limited. Here, we explored the effects of 17β-estradiol (E2) on apoptosis of various liver cell lines (LO2, HepG2, and HepG2.2.15 cells). Within a certain concentration range, 17β-estradiol induced oxidative stress and apoptosis of HepG2 cells, downregulated ERα-36 expression, and increased Akt and Foxo3a phosphorylation. p-Foxo3a became localized around the nucleus but did not enter the organelle. The levels of mRNAs encoding manganese superoxide dismutase (MnSOD) and catalase, to the promoters of which Foxo3a binds to trigger gene expression, were significantly reduced in HepG2 cells. 17β-estradiol had no obvious effects on LO2 or HepG2.2.15 cells. We speculate that 17β-estradiol may induce oxidative stress in HepG2 cells by increasing Foxo3a phosphorylation, thus promoting apoptosis. This may serve as a new treatment for hepatocellular carcinoma.